Understanding employees' energy saving in the workplace: DR and the Philippines' realities - Luis J. Camacho; Michael Pasco; Moises Banks; Randall Pasco; Marisela Almanzar; Alvin Rodriguez; Akinlawon Amoo; Nelda Rosima (Journal of Risk and Financial Management, 2023)
Understanding how employees act at work to save energy and the meaning for sustainability and environmental protection is essential. This research aimed to analyze the influences of Subjective Norms (SN), Descriptive Norms (DN), and Environmental Knowledge (EK) on employees' intention to save energy (ISE) in the Philippines (PH) and the Dominican Republic (DR). The effects of SN, DN, and EK on ISE were evaluated by comparing two developing countries and the mediation effect of EK on the relationship between DN, SN, and ISE. Confirmatory factor analysis (CFA), followed by structural equation modeling and path analysis based on samples collected from employees from DR (340) and PH (339), was performed. Also, construct convergent and discriminant validity were assessed using composite reliability, maximal reliability, average variance extracted, and maximum shared variance. The findings of this study indicate that SN influences ISE positively among employees in PH (Ø = 0.15, p < 0.05) but not among employees in DR. Descriptive Norms positively influence ISE among employees in PH (Ø = 0.47, p < 0.01) and DR (Ø = 0.27, p < 0.01), while EK has a positive and significant influence on the ISE among employees in PH (Ø = 0.22, p < 0.01) and not in DR. There is a partial mediation effect between SN and EK on ISE when EK is the mediator in PH, and no mediation effects for RD. The intention to save energy is significant in economic terms because reducing energy consumption can help decrease energy costs and improve business profitability and competitiveness; in social terms, it can reduce energy consumption worldwide and improve social health, reducing gas emissions and pollution.
Keywords: 650; subjective norms; descriptive norms; energy saving; environmental knowledge; intention to save energy